2017
DOI: 10.1007/s00431-017-2993-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between infantile postural asymmetry and unsettled behaviour in babies

Abstract: Questions remain regarding the construct validity of the infantile postural asymmetry scale. No association between unsettled infant behaviour and infantile postural asymmetry was found in 12- to 16-week-old infants. The influence of sex on the interaction between infantile postural asymmetry and infant behaviour needs further examination. An association between unsettled infant behaviour and infantile postural asymmetry is still unproven. What is known: • Unsettled infant behaviour has a considerable impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There is more access to research on the body posture of children with various motor and nervous system problems that begin in infancy. Idiopathic asymmetry is sometimes considered a trivial medical problem that should undergo auto-correction in the course of development [ 22 , 23 , 24 ]. However, among a large group of children, the beginnings of incorrect posture, or rather movement/postural patterns, were visible from the first weeks of life.…”
Section: Discussionmentioning
confidence: 99%
“…There is more access to research on the body posture of children with various motor and nervous system problems that begin in infancy. Idiopathic asymmetry is sometimes considered a trivial medical problem that should undergo auto-correction in the course of development [ 22 , 23 , 24 ]. However, among a large group of children, the beginnings of incorrect posture, or rather movement/postural patterns, were visible from the first weeks of life.…”
Section: Discussionmentioning
confidence: 99%
“…However this relies largely on evidence-informed guidance and parental compliance to optimal infant positioning and handling strategies 39 . Studies have also shown favourable outcomes for targeted parent education strategies in reducing the prevalence of PA and HSA 2 with a reliance on clear and consistent information to ensure parental adherence 33,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement scales for PA have been proposed 31,32 . However issues with validity were identi ed 33 and these remain little utilised.…”
Section: Introductionmentioning
confidence: 99%